Techniques of Maximum Power Point Tracking by Using Perturb and Observe and Lookup Table Methodologies - Yuttikarn Lapkitticharoenchai; Anuwat Jangwanitlert (International Review of Electrical Engineering (IREE), 2025)
In the typical Photovoltaic (PV) system, the Perturb and Observe (P&O) technique is the algorithm that is used for tracking the Maximum Power Point (MPP). It enables the photovoltaic (PV) panel to reach the maximum power output. However, there are two main existing problems which are the slow speed of the P&O, and an oscillation of power around MPP. The problems lead to a reduction of the power output of the PV panel. This paper presents a new hybrid methodology for a faster Maximum Power Point Tracking (MPPT) application. The proposed method consists of the Lookup Table, together with the P&O techniques. The results show that the Lookup Table employs measured values of an irradiance, a temperature, and a Duty Cycle to achieve MPPT precisely. Consequently, the Lookup Table’s tracking speed is significantly faster than P&O and the oscillation of tracking power is eliminated. Moreover, the new hybrid methodology also uses P&O to record irradiance, temperature, and Duty Cycle data into the table. Once sufficient data are collected and under defined the conditions, the system automatically select to the Lookup Table for operation.
Keywords: Photovoltaic System Optimization Techniques; Solar Radiation and Photovoltaics; Solar Thermal and Photovoltaic Systems